Gelation behavior as a function of concentration of sodium thiosulfate for PAM gels cross-linked with chromium - Al-Hajri, Sameer; Mahmood, Syed M.; Akbari, Saeed; Abdulelah, Hesham (Journal of Petroleum Exploration and Production Technology, 2019)
Existing reducing agents for cross-linking polymers are expensive and toxic and mostly limited for water shut off applications. A gelation study was performed on a safer, cheaper, more soluble, and short-lived gel by cross-linking polyacrylamide and chromium as a cross-linking agent using a rheometer and bead-pack porous media. The effect of concentration of sodium thiosulfate as the reducing agent was investigated to determine conditions for optimum yield strength and the gelation time and behavior which has never been published before. For a fixed minimum concentration (for the gel to form) of polyacrylamide and sodium dichromate, the gel yield strength vs. sodium thiosulfate concentration showed a somewhat bell-shaped curve initially increasing, reaching a peak at 2000 ppm, and then starting to decrease. The gelation formed by sodium thiosulfate was comparatively weak and short lived as compared to the ones formed by other reducing agents. Gel started to form instantaneously, reached a peak in 2 h, began to decrease, and then stabilized at 40 cp. The mobility reduction trends were similar to the yield strength curve. The short-lived gel could be useful to improve the waterflood mobility ratio far away from the wellbore without compromising on ease of injectivity.